PENGGUNAAN LILIN UNTUK MEMPERPANJANG UMUR SIMPAN BUAH NAGA MERAH (Hylocereus polyrhizus) - Noviar Harun; Raswen Efendi; Saddam Husein Hasibuan (Jurnal Sagu, 2012)
The aim of this study was to determine the effect of variaus concentration of wax emulsion onthe shelf life of red dragon fruit (Hylocereus polyrhizus). This study was done at the Laboratory ofAnalysis of Agricultural Products, Faculty of Agriculture, University of Riau. The design used in thestudy was completely randomized design (CRD) with 5 treatments and 4 replications. Treatments wereperformed during the study were L1: No wax emulsion; L2: Application of 2% wax emulsion; L3:Application of 4% wax emulsion; L4: Application of 6% wax emulsion; L5: Application of 8% waxemulsion. The data formed were statistically analyzed with analysis of variance. Parameter absorvedwere total dissolved solid, weight shrinkage, respiration rate and organoleptic tests including skinand flesh colors, flavor and aroma. Use of wax emulsion significantly affected the weight, moisturecontent, textue, flash and skin colors and teste, but did not significantly influence the dissolved totalsolid, respiration rate, and aroma of rad dragon fruit. The best treatment found when 6% of waxemulsion applied.Key words: dragon fruit, wax, combined